A checklist of Branchiopoda (Anostraca and Cladocera) of Chilean continental waters - Escalante, Patricio De Los Rios; Kotov, Alexey A. (Zootaxa, 2015)
The aim of the present study is to represent an annotated checklist of the Branchiopoda (Crustacea) reported from Chilean inland waters. Only Anostraca and Cladocera are found in Chile, while there are no reports on Notostraca and "Conchostraca". Our checklist contains 85 valid taxa, among which nine anostracans and 76 cladocerans. Such "low" biodiversity of the branchiopods in Chile is in reality an artifact of insufficient sampling. Our work indicates that more faunistic, taxonomic and biogeographical studies of Chilean branchiopods are necessary, especially in areas with subtropical climate, Atacama desert, Southern Patagonia, and central Chilean ephemeral pools.